EFFECTS OF MACROECONOMIC VARIABLES ON STOCK MARKET PERFORMANCE IN NIGERIA: 1986 – 2020 - Okoebor, Sylvester Ebosetale (African Journal of Social and Behavioural Sciences, 2022)
The study examined the effects of macroeconomic variables on stock market performance in Nigeria between 1986 – 2020. The variables considered in this paper were; All Share Price Index, private sector credit, exchange rate, interest rate and inflation. The study investigated the influence of these variables on stocks and the ultimate implications on investor’s decisions and the general economy. The study adopted expo facto research design using secondary data sourced from Nigeria bureau of statistics, World Bank data catalogue and Nigerian stock exchange as variables used from a scope of 1986-2020. The work uses Ordinary Least Square Regression (OLS) statistical technique method. The tools adopted are, Descriptive statistics, Unit root, Heterocedasticity, and Johansson co-integration to test the normality, stability, Homocedasticity and long run relationships between variables. Some of the variables showed significant influence on stock market performance from the analysis thereby, giving credence to positive relationship between macroeconomic variables and stock market performance in Nigeria. Findings indicated that, private sector credit, exchange and interest rate has significant effects on all share indexes while Inflation on the other hand has a negative insignificant influence on all share indexes respectively. The regression results showed a strong relationship between macroeconomic variables and stock market performance in Nigeria. The implications are; policy makers benefits from the spill over information arising from market activities to give priority attention to reforms that activates a vibrant stock market performances. The study recommended that, Government should start the process of implementing special intervention policies that could enhance broad base stock market dominance through monetary instruments to be implemented by financial institutions.